Dual-energy lung perfusion in portal venous phase CT—A comparison with the pulmonary arterial phase - Praël, Isabelle; Wuest, Wolfgang; Heiß, Rafael; Wiesmüller, Marco; Kopp, Markus; Uder, Michael; May, Matthias (Diagnostics, 2021)
Pulmonary arterial dual-energy (aDE) CT is an established technique for evaluating pulmonary perfusion blood volume (PBV). As DECT protocols are increasingly used for thoracoabdominal CT, this study assessed image quality and clinical findings in portal–venous phase dual-energy (vDE) CT and compared it to aDE. In 95 patients, vDE-CT was performed using a dual-source scanner (70/Sn150 kV, 560/140 ref.mAs). Pulmonary triggered aDE-CT served as reference (n = 94). PBV was reconstructed using a dedicated algorithm. Mean relative attenuation was measured in the pulmonary trunk, aorta, and segmented lung parenchyma. A distribution ratio (DL) between vessels and parenchyma was calculated to assess the iodine uptake of the lung parenchyma. Subjective overall diagnostic image quality was assessed for PBV images on a five-point Likert scale. Image artifacts were classified into five groups based on scale rating and compared between vDE and aDE. Pathological findings were correlated with the anatomical image datasets. Mean relative attenuation of the lung parenchyma was comparable in both groups (vDE: 23 ± 6 HU and aDE: 22 ± 7 HU), but significantly lower in the vessels of vDE. Therefore, iodine uptake of the lung parenchyma was significantly higher in vDE (DL: 10% vs. 8%, p < 0.01). The subjective overall image quality of the PBV images was comparable (p = 0.5). Rotation and streak artifacts were found in most of the patients (>86%, both p > 0.6). Dual-source artifacts were found in only a few patients in both groups (vDE 5%, aDE 7%, p = 0.5). Recess and subpleural artifacts were increased in vDE (vDE 53/27%, aDE 24/7%, both p < 0.001). Pathological findings were found in 19% of the vDE patients and 59% of the aDE patients. Comparable objective and subjective image quality of lung perfusion can be obtained in vDE and aDE. Iodine uptake of the lung parenchyma is increased in vDE compared to aDE, suggesting an interstitial pooling effect. Knowledge of the different appearances of artifacts will aid in the interpretation of the images. Additional clinical information about the lung parenchyma can be provided by PBV evaluation in vDE.
CRIS-Team Scopus Importer:2021-11-19
Keywords: Dual-energy computed tomography; Lung perfusion; Portal venous